USING RPG VIDEO GAMES TO IMPROVE ENGLISH VOCABULARY ACHIEVEMENT OF THE 8th GRADERS OF SMP LTI IGM PALEMBANG - IRFAN IRFAN; DIEMROH IHSAN; ISMAIL PETRUS (Sriwijaya University Learning and Education International Conference, 2016)
The objectives of this study were to find out: (1) whether or not there was any significant improvement in students’ English vocabulary achievement after they were taught by using Role-Playing Game (RPG) Video Games and (2) the students’ perceptions on using RPG video games in learning English vocabulary. This study involved 20 eighth grade students. However, only 14 students were taken as the sample for the vocabulary tests and 19 students as the sample for the preference questionnaire due to the students’ absence during the vocabulary test and questionnaire administration. To collect the data, the students were given 4 vocabulary tests consisting of a pre-test, two progress tests, and a post-test, as well as a preference questionnaire which were analyzed by using paired sample t-test and percentage procedure. The findings showed that: (1) there was a significant improvement in the students’ vocabulary achievement between the pre-test and the post-test (p=0.000 < α=0.05) and (2) 95% of the students preferred using RPG video game to study English vocabulary. In conclusion, RPG video game was effective and preferable to be used in teaching vocabulary for the eighth grade students of SMP LTI IGM Palembang.